Prevention and Therapy of Preterm Birth. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry Number 015/025, September 2022) – Part 2 with Recommendations on the Tertiary Prevention of Preterm Birth and on the Management of Preterm Premature Rupture of Membranes - Berger, Richard; Abele, Harald; Bahlmann, Franz; Doubek, Klaus; Felderhoff-Müser, Ursula; Fluhr, Herbert; Garnier, Yves; Grylka-Baeschlin, Susanne; Hayward, Aurelia; Helmer, Hanns; Herting, Egbert; Hoopmann, Markus; Hösli, Irene; Hoyme, Udo; Kunze, Mirjam; Kuon, Ruben-J.; Kyvernitakis, Ioannis; Lütje, Wolf; Mader, Silke; Maul, Holger; Mendling, Werner; Mitschdörfer, Barbara; Nothacker, Monika; Olbertz, Dirk; Ramsell, Andrea; Rath, Werner; Roll, Claudia; Schlembach, Dietmar; Schleußner, Ekkehard; Schütz, Florian; Seifert-Klauss, Vanadin; Stubert, Johannes; Surbek, Daniel (Geburtshilfe und Frauenheilkunde, 2023)
Aim The revision of this guideline was coordinated by the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (OEGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). The aim of the guideline is to improve the prediction, prevention and management of preterm birth based on evidence from the current literature, the experience of members of the guidelines commission, and the viewpoint of self-help organizations.Methods The members of the contributing professional societies and organizations developed recommendations and statements based on international literature. The recommendations and statements were presented and adopted using a formal process (structured consensus conferences with neutral moderation, written Delphi vote).Recommendations Part 2 of this short version of the guideline presents statements and recommendations on the tertiary prevention of preterm birth and the management of preterm premature rupture of membranes.Ziel Überarbeitete Leitlinie der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG), der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG) und der Schweizerischen Gesellschaft für Gynäkologie und Geburtshilfe (SGGG). Ziel der Leitlinie ist es, die Prädiktion, die Prävention und das Management der Frühgeburt anhand der aktuellen Literatur, der Erfahrung der Mitglieder der Leitlinienkommission einschließlich der Sicht der Selbsthilfe evidenzbasiert zu verbessern.Methoden Anhand der internationalen Literatur entwickelten die Mitglieder der beteiligten Fachgesellschaften und Organisationen zahlreiche Empfehlungen und Statements. Diese wurden in einem formalen Prozess (strukturierte Konsensuskonferenzen mit neutraler Moderation, schriftliche Delphi-Abstimmung) verabschiedet.Empfehlungen Der Teil 2 dieser Kurzversion der Leitlinie zeigt Statements und Empfehlungen zur tertiären Prävention der Frühgeburt sowie zum Management des frühen vorzeitigen Blasensprungs.
Keywords: guideline; preterm birth; preterm labor; cervical insufficiency; preterm premature rupture of membranes